Isolation and functional analysis of MdNAS1, with functions in improved iron stress tolerance and abnormal flower in transgenic tobacco. Issue 1 (1st January 2018) - Han, Deguo; Hou, Yanjie; Liu, Wei; Zhang, Zhaoyuan; Ding, Haibin; Li, Hongxia; Yang, Guohui
ABSTRACT: Metal elements are essential micronutrients required by all plants for natural physiological activities. Nicotianamine is considered as the chelate substance in the transport of metal ions. In the present study, a new gene encoding NA synthase was isolated from Malus domestica (L.) Borkh and designated as MdNAS1 . The expression levels of MdNAS1 were enriched in leaf, and phloem which were highly affected by Fe stress, indoleacetic acid (IAA) and abscisic acid (ABA) treatments in M. domestica seedlings. Subcellular localization research revealed that MdNAS1 was localized in cytoplasmic membrane. Overexpression of MdNAS1 in transgenic tobaccos increased the tolerance to Fe stress, but also contributes to higher chlorophyll, NA, Fe, Mn, Cu and Zn contents and abnormal flowers. Moreover, the MdNAS1 -OE tobaccos had the increased expression levels of Fe uptake and transport related genes ( NtFRO, NtIRT1, NtVIT, NtNRAMP1, and NtYSL ).